2016
DOI: 10.1016/j.drugalcdep.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk scores for cigarettes smoked per day do not generalize to a Native American population

Abstract: Background Recent studies have demonstrated the utility of polygenic risk scores (PRSs) for exploring the genetic etiology of psychiatric phenotypes and the genetic correlations between them. To date, these studies have been conducted almost exclusively using participants of European ancestry, and thus, there is a need for similar studies conducted in other ancestral populations. However, given that the predictive ability of PRSs are sensitive to differences in linkage disequilibrium (LD) patterns and minor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In Appendix A, we show that the polygenic score is positively correlated with and predicts smoking behavior in non-whites. This is confirmed by other studies that show overlapping SNPs in smoking GWAS conducted on African and European ancestry populations (Otto et al, 2016).…”
Section: Methodssupporting
confidence: 88%
“…In Appendix A, we show that the polygenic score is positively correlated with and predicts smoking behavior in non-whites. This is confirmed by other studies that show overlapping SNPs in smoking GWAS conducted on African and European ancestry populations (Otto et al, 2016).…”
Section: Methodssupporting
confidence: 88%
“…With the exception of the summary data on BMI, which was from a multi-ethnic sample, all GWAS summary statistics were derived from European populations. While these negative results may in part be due to the factors listed above (e.g., phenotype definition, limited power, and limited number of imputed variants), the predictive ability of GRSs are sensitive to differences in LD and MAF across base and target samples and previous work on our AI sample indicated that GRSs for smoking behaviors from a European population were only predictive in our sample for those subjects with a high proportion of European ancestry (Otto et al, 2016). The findings presented above highlight the need for both replication and large-scale studies of these minority populations to probe for ethnic-specific genetic risk factors and endophenotypes for complex diseases.…”
Section: Discussionmentioning
confidence: 79%
“…These studies have identified correlations between the genetic risk of schizophrenia and substance use and have selected genetically correlated loci as a proxy for the genetic risk of comorbidity. [14][15][16][17][18] Schizophrenia-associated loci are highly correlated with substance use, and individuals with a higher genetic risk also have a higher prevalence of schizophrenia according to genetic risk scores (i.e., the score is estimated by the schizophrenia-associated variants an individual carries, pondered by the estimated effect in genome-wide association studies). 17,19 Therefore, the variants used to define the genetic score for schizophrenia are also of great interest due to their association with comorbid substance use.…”
Section: Introductionmentioning
confidence: 99%